GIANT LIVER FLUKE IN NORTH DAKOTA MOOSE - Maskey, James Joseph (Lakehead University, 2011)
The giant liver fluke (Fascioloides magna) is a parasite of white-tailed deer (Odocoileus virginianus) and wapiti (Cervus elaphus) that can cause extensive and conspicuous liver damage in moose (Alces alces), a dead-end host. The implication of F. magna as a factor in the long-term decline of moose in northwestern Minnesota has raised concern that a concurrent decline in moose in northeastern North Dakota may also be linked to this parasite. I reviewed data collected from moose hunter check stations in1977-1984 and necropsy reports of non-harvested animals examined in 1983-1992 to estimate past prevalence of F. magna in moose in North Dakota. I also collected livers from harvested moose in 2002 and 2003 to investigate the current occurrence of this parasite. I also surveyed 78 wetlands at 12 sites in 2003-2006 to examine the potential for F. magna transmission based on the occurrence of aquatic snail intermediate hosts. Flukes or signs consistent with fluke infection were observed in 19.6% of harvested moose (n = 158) in 1977-1984, and in 18.8% of moose necropsied (n = 32) in 1983-1992. Fascioloides magna was not recovered from any of the 78 moose livers collected in 2002 and 2003. However, lymnaeid snails were found at 10 of 12 sites in the aquatic gastropod surveys indicating that the intermediate hosts for this parasite occur widely throughout the range of moose in North Dakota. While this represents the first known report of F. magna in North Dakota, this parasite occurs at relatively low prevalence, and there is no evidence that it has been an important factor in recent moose declines, nor that it noticeably impairs the health of moose in North Dakota. Transmission may be limited by the transient availability of wetlands capable of supporting the life cycle of F. magna.